Makna Upacara Tabar Kampung Ulungali Manggarai Dalam Terang Filsafat Fenomenologi Heidegger - Darus, Yulius; Datus, Paskalis (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The focus of this paper is to explore the philosophical meaning and values behind the Tabar ceremony of the Ulungali community in Manggarai-Flores, NTT. The methodology employed in this paper is the phenomenological philosophical approach, where the author delves into philosophical matters related to local wisdom, particularly the Tabar ceremony, and connects it with the phenomenological philosophy of Heidegger. The approach used to explore the Tabar ceremony is qualitative, drawing from various literary sources and conducting interviews. The objectives of this paper are twofold. First, to gain a deeper understanding of the philosophical meaning behind the local wisdom of the Tabar ceremony in the Ulungali Manggarai community in relation to Heidegger's phenomenological philosophy. Second, to raise awareness among individuals to build a pattern of subject-subject relations or